The role of p38alpha in Schwann cells in regulating peripheral nerve myelination and repair. Issue 1 (13th January 2017) - Roberts, Sheridan L.; Dun, Xin‐peng; Dee, Gemma; Gray, Bethany; Mindos, Thomas; Parkinson, David B.
Abstract: Myelination in the peripheral nervous system (PNS) is controlled by both positive and negative regulators within Schwann cells to ensure timely onset and correct myelin thickness for saltatory conduction by neurons. Transcription factors such as Sox10, octamer‐binding transcription factor 6 (Oct6) and Krox20 form a positive regulatory network, whereas negative regulators such as cJun and Sox2 oppose myelination in Schwann cells. The role of the p38 MAPK pathway has been studied in PNS myelination, but its precise function remains unclear, with both positive and negative effects of p38 activity reported upon both myelination and processes of nerve repair. To clarify the role of p38 MAPK in the PNS, we have analysed mice with a Schwann cell‐specific ablation of the major p38 isoform, p38alpha. In line with previous findings of an inhibitory role for p38 MAPK, we observe acceleration of post‐natal myelination in p38alpha null nerves, a delay in myelin down‐regulation following injury, together with a small increase in levels of re‐myelination following injury. Finally we explored roles for p38alpha in controlling axonal regeneration and functional repair following PNS injury and observe that loss of p38alpha function in Schwann cells does not appear to affect these processes as previously reported. These studies therefore provide further proof for a role of p38 MAPK signalling in the control of myelination by Schwann cells in the PNS, but do not show an apparent role for signalling by this MAP kinase in Schwann cells controlling other elements of Wallerian degeneration and functional repair following injury. Cover Image for this issue: doi:10.1111/jnc.13793 . Abstract : Using Schwann cell‐specific p38α null mice, we aimed to clarify and characterise the functional role of p38α on peripheral nerve myelination in vivo . Here, we demonstrate for the first time in vivo that p38α functions as a negative regulator of myelination. Specific depletion of p38α in Schwann cells results in accelerated myelination and myelin protein expression during development, as well as early delays in Schwann cell demyelination and myelin protein degradation following nerve injury. Cover Image for this issue: doi:10.1111/jnc.13793 .